Design of the low-voltage CMOS analog multiplier - Chong, Hauo Wah. (2010)
Analog Multiplier is an electronic device that performs linear multiplication of two continual input signals. It found its extensive uses in analog signal processing. In this report, different architectures of multipliers reported are discussed. Advantages and disadvantages of each topology were studied before the final design was proposed.